Evaluation of lean practices in warehouses: an analysis of Brazilian reality - Caroline Pereira and Rosley Anholon and Izabela Simon Rampasso and Osvaldo Luiz Goncalves Quelhas and Walter Leal and Luis Antonio de Santa-Eulalia (The international journal of productivity and performance management : IJPPM, 2020)
Purpose